2010
DOI: 10.1371/journal.pone.0010687
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphate Predicts Early Mortality in Adults Starting Antiretroviral Therapy in Lusaka, Zambia: A Prospective Cohort Study

Abstract: BackgroundPatients starting antiretroviral therapy (ART) for acquired immunodeficiency syndrome (AIDS) in sub-Saharan Africa have high rates of mortality in the initial weeks of treatment. We assessed the association of serum phosphate with early mortality among HIV-infected adults with severe malnutrition and/or advanced immunosuppression.Methodology/Principal FindingsAn observational cohort of 142 HIV-infected adults initiating ART in Lusaka, Zambia with body mass index (BMI) <16 kg/m2 or CD4+ lymphocyte cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…We previously reported that the absolute value of one-week serum phosphate and the change from the pre-treatment level were not significantly associated with mortality in this cohort, as might be observed in the refeeding syndrome [13]. This condition is classically defined by electrolyte and fluid shifts over a period of several weeks in response to increased carbohydrate intake among nutritionally depleted individuals, which predisposes to a range of cardiovascular, respiratory and neurologic sequelae, and death [14,15,29].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We previously reported that the absolute value of one-week serum phosphate and the change from the pre-treatment level were not significantly associated with mortality in this cohort, as might be observed in the refeeding syndrome [13]. This condition is classically defined by electrolyte and fluid shifts over a period of several weeks in response to increased carbohydrate intake among nutritionally depleted individuals, which predisposes to a range of cardiovascular, respiratory and neurologic sequelae, and death [14,15,29].…”
Section: Discussionmentioning
confidence: 88%
“…The study setting, eligibility criteria, design and procedures have been previously described [13]. Briefly, individuals were eligible for enrolment if they: qualified for ART according to Zambian national guidelines in place at the time (i.e., WHO stage 4 disease, a CD4 + lymphocyte count below 200 cells/mm 3 , or WHO stage 3 disease and a CD4 + lymphocyte count below 350 cells/mm 3 ); were intending to start therapy the same day; met the BMI and/or CD4 + threshold criteria; and agreed to adhere to the study visit schedule and laboratory testing requirements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first principal component was extracted for age, BMI, square root of CD4+ lymphocyte count, hemoglobin, and phosphate using the ‘princomp()’ function from the covariance matrix in R software. We adjusted for serum phosphate due to our prior finding that hypophosphatemia is an independent predictor of early mortality in this population (23) . If a participant had no recorded appetite or intake values within a given time interval, he or she was dropped from the risk set for that interval.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…GroPCho Utilization under Serum Growth Conditions-To explore GroPCho transport under conditions more similar to those experienced in a human host, we performed GroPCho incorporation experiments in the presence of 10% serum and 1 mM KH 2 PO 4 , which is within the phosphate concentration range reported for serum (42). Cultures were grown for 6 h at 37°C in the presence of [ 3 H]GroPCho, and the internal metabolites were analyzed (Fig.…”
Section: Kinetics Of Gropcho Transport By Git3 and Git4-givenmentioning
confidence: 99%